HUBUNGAN STATUS GIZI, KONSUMSI MAKANAN BERLEMAK, KONSUMSI MINUMAN MANIS DENGAN KEJADIAN DISMENOREA DI WONOKROMO SURABAYA - Al Fadlil, Muthi’atuz Zahroh (Jurnal Gizi dan Kesehatan Nusantara, 2023)
Hip discomfort that develops during the some of first months or years the menstruation is known as primary dysmenorrhoea. Nutritional status and a diet high in calories, fat, carbs, and lack of fiber, such as fried (fatty) meals, are risk factors that affect the development of primary dysmenorrhoea. The purpose of this study is to ascertain how dietary intake, consumption of fatty foods, and consumption of sugary beverages correlate with the prevalence of dysmenorrhea. This research is a correlational quantifiability with cross sectional type design. The subjects in this research were women aged 15-25 years with a total of 97 people. In this study, chi-square analysis was used with a meaningfulness level of a = 0,05. The results of research on the correlation between nutritional condition and dysmenorrhea incidence showed a p value (0.016) meaning that there was a correlation between nutritional condition and dysmenorrhea incidence. In the correlation between the frequency of consumption of fatty foods and dysmenorrhea incidence, p value (0.000) was obtained which indicated that there was a relevant relationship between the frequency of fatty foods and dysmenorrhea incidence. In the correlation between the frequency of consumption of sweet drinks and dysmenorrhea incidence, p value (0.000) is obtained, which means that there is a correlation between the frequency of consumption of sweet drinks and dysmenorrhea incidence. It was found that there is a relevant correlation between nutritional condition and dysmenorrhea incidence, correlation between the frequency of fatty food consumption and dysmenorrhea incidence, and correlation between the frequency of sweet drinks and dysmenorrhea incidence in women aged 15-25 years at Wonokromo Health Center Surabaya Working Area.